Early Recurrence of Ovarian Cancer during Pregnancy after Primary Staging Surgery in the First Trimester - Munetoshi Akazawa; Kazunori Hashimoto (Case Reports in Obstetrics and Gynecology)
Cancer during pregnancy is rare. However, even during pregnancy, there is the possibility of recurrence for the patients. We present the case of recurrence of ovarian cancer during pregnancy regardless of primary staging surgery performed in the first trimester of the same pregnancy. The patient was a 29-year-old woman who underwent fertility-sparing surgery at 15 weeks of pregnancy for ovarian cancer (mucinous adenocarcinoma, FIGO stage IC). Omitting adjuvant chemotherapy during pregnancy, we continued the prenatal checkups in the outpatient. At 31 weeks of gestation, massive ascites emerged and oliguria/anuria developed acutely. We performed emergent cesarean section, diagnosing acute kidney injury during pregnancy. On surgical finding, there were a number of 1 cm sized nodules in the small bowel wall and peritoneum. The infant was appropriate for gestational age without any abnormalities. Oliguria continued due to rapid accumulation of ascites in the early postpartum period. After two cycles of chemotherapy, ascites decreased gradually and the markers gradually decreased. However, after six courses of chemotherapy, she suddenly complained of nausea and anorexia. CT imaging showed cancerous ileus and ascites fluids. The patient chose palliative care. Even in the case of nonadvanced cancer, it has the potential to be an extremely aggressive malignancy under the irregular hormonal environment of pregnancy.